Under The Umbrella of International Law, Violence and Rape in Armed Conflicts - Ali, Yasir (Journal of Legal Sciences, 2025)
The current series of wars and the violence and rape committed by entities and states have prompted me to think about researching how violence and rape can fall under the umbrella of my specialization in public international law. The wars in Gaza and Ukraine have highlighted the importance of individual freedom from state violence and armed entities, which has been affirmed in human rights for all without discrimination on the basis of race, gender, language or religion, while international law has developed and developed specialized systems related to human rights and international criminal law alongside international humanitarian law to prevent and protect against violence. However, most international resolutions have become in an international legal vacuum; they refer to and rely on the three legal systems - international humanitarian law, international criminal law and human rights. This research addressed the concepts of violence and rape in armed conflict and thus touched on the various international legal systems that prohibit it and the national measures that restrict it. Pointing to the violations and historical precedents that occurred according to the inductive approach by analyzing the facts, until the weakness in accountability on the one hand and the increase in violations and the fragility of treatments on the other hand became clear, so that the research reached a conclusion and specific recommendations.